2020
DOI: 10.1002/path.5537
|View full text |Cite
|
Sign up to set email alerts
|

Drivers underpinning the malignant transformation of giant cell tumour of bone

Abstract: The rare benign giant cell tumour of bone (GCTB) is defined by an almost unique mutation in the H3.3 family of histone genes H3-3A or H3-3B; however, the same mutation is occasionally found in primary malignant bone tumours which share many features with the benign variant. Moreover, lung metastases can occur despite the absence of malignant histological features in either the primary or metastatic lesions. Herein we investigated the genetic events of 17 GCTBs including benign and malignant variants and the me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 32 publications
3
28
1
Order By: Relevance
“…Our work and that of others on DNA methylation profiling of sarcoma has demonstrated key insights into specific tumour types [6][7][8][9][10][11], and has shown that DNA methylation can add value to whole-genome and RNA sequencing data. To enhance the benefit of the genomes delivered from 1,200 patients with sarcoma as part of the UK's 100,000 Genomes Project [12], we have undertaken methylation profiling of a significant proportion of these patients' samples, with the aim of providing greater insight into the pathogenesis of sarcoma and its mimics.…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations
“…Our work and that of others on DNA methylation profiling of sarcoma has demonstrated key insights into specific tumour types [6][7][8][9][10][11], and has shown that DNA methylation can add value to whole-genome and RNA sequencing data. To enhance the benefit of the genomes delivered from 1,200 patients with sarcoma as part of the UK's 100,000 Genomes Project [12], we have undertaken methylation profiling of a significant proportion of these patients' samples, with the aim of providing greater insight into the pathogenesis of sarcoma and its mimics.…”
Section: Introductionmentioning
confidence: 74%
“…DNA methylation profiling data were available from 986 samples; many of the samples were included in other studies over the last 5 years including the 100,000 Genomes Project [6][7][8][9]13]. For details of generation of these data, see Supplementary materials and methods.…”
Section: Dna Methylation Data Setmentioning
confidence: 99%
See 2 more Smart Citations
“…Next to histological examination, interpretation of the radiological features may be of major help in distinguishing both entities. Molecularly, a recent publication reported that maligant bone tumours with a H3.3-G34W mutation possess features resembling osteosarcoma [105]. More specifically, they carry an increased burden of somatic mutation variants.…”
Section: H33-g34w and Malignant Gctbmentioning
confidence: 99%